International Criminal Law Analysis of The Israeli Military Attack on The Garuda Contingent Headquarters in Lebanon - Tihadanah Tihadanah; Rabith Madah Khulaili Harsya; Bambang Julianto; Diana Pujiningsih; Ma’rifah Ma’rifah (Journal Of Human And Education (JAHE), 2026)
The Israeli Defense Forces (IDF) military attack targeting the Garuda Indonesia Contingent Headquarters of the United Nations Interim Force in Lebanon (UNIFIL) mission in South Lebanon has sparked serious debate in international legal discourse. This study aims to analyze the incident from the perspective of International Criminal Law and International Humanitarian Law (IHL). Using normative legal research methods through a statute approach and a case approach, this article examines whether the attack can be categorized as a war crime under the jurisdiction of the 1998 Rome Statute. The results of the analysis indicate that UN peacekeeping personnel have the status of protected civilians as long as they are not directly involved in hostilities. Therefore, the deliberate attack on the Garuda Contingent headquarters constitutes a serious violation of the 1949 Geneva Convention and UN Security Council Resolution No. 1701. This study concludes that the act fulfills the material elements (actus reus) and mental elements ( mens rea ) of war crimes, which give rise to individual criminal responsibility for the military commanders involved and demands law enforcement through international mechanisms to maintain the dignity of the UN collective security system.